(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to explore and develop effective strategies to enhance intergroup behavior in the school environment. A quantitative approach was employed in this study using a survey research design and data collection techniques through direct observation. The population of this study consisted of primary school students in a specific area, with a randomly selected sample. The results of the study indicate that factors such as interpersonal perception, self-concept, and student social interactions significantly influence intergroup cooperation in schools. The implications of these findings for the development of more inclusive and collaborative educational practices are also discussed. Recommendations are made to strengthen intergroup cooperation through regular training programs and collaborative activities held in schools